Brazil’s landless hold their ground - Vanden (Autor), Harry E.; Marin (Tradutor), Pedro de Lima (Universidade Estadual Paulista / UNESP, 2008)
This article analyses the Brazilian Landless Workers Movement in a comparative approach with the similar movements in Latin America as a continent still ruled by a neoliberal policies. For this purpose, the text focus the secular process of land’s concentration and the peasantry’s marginal conditions perpetrated by the dominant elites in order to relate it to the recent process characterized by the disenchantment towards the traditional representative institutions experienced by a broad segments of the population submitted to the globalization. Based in this background, the Landless Workers Movement as well as others social movements are eager to strength the mechanisms of participative democracy and also the modes of political action in Brazil and Latin America.